Anatomical study on the kidney of musk deer (Moschus moschiefrus) - SUDHAN, N A; SURI, SHALINI; SARMA, K; AZMI, S; KUMAR, P (The Indian Journal of Animal Sciences, 2011)
One young (4 month of age) female musk deer comprised the study material in the present investigation. Both the kidneys were placed at the sublumbar region with the left one placed posterior to the right one. Both were bean shaped, smooth surfaced with no superficial vascularization. The capsule of both the kidneys was exceptionally thick. The left kidney had flat ruminal surface. The hilus was located at the middle of the medial surface in both the kidneys. Longitudinal section revealed outer darker cortex and inner paler medulla. No para cortex and renal column was observed. The renal sinus was well developed which gave a “H” shape. The renal pelvis was less developed and half moon shaped. The parenchymatus structures of the right kidney had many differences with its left counterpart. Maximum biometrical parameters recorded in the right kidney were more than the left one rendering it larger and heavier.